Whose Authority May I Ask? Polish, English, German, Shakespearean or Directorial? On the Boundaries Between Ethnicity, Nationality, Religion and Theatricality in Jan Klata’s Shakespearean Productions - Fabiszak, Jacek (Multicultural Shakespeare: Translation, Appropriation and Performance, 2018)
Jan Klata is a director who has been labelled a provocateur and who is considered to hold nothing cultural or national sacred. From the beginning of his artistic career he is said to have challenged authorities: theatrical, ethnic, national, etc. by debunking and questioning prevailing heroic myths and forms. Today, imperceptibly yet steadily, Klata himself becomes an authority and his theatrical productions gradually become classics in the eyes of the new generations of theatre directors and audiences, at the same time inciting and inevitably inviting cultural rebellion ... The article examines Klata’s treatment of theatrical and national authority in his Shakespeare productions, on the one hand, and the image of the director as an authority on the other. All in the light of the theoretical model on authority in theatre, especially in Shakespeare productions, developed by W.B. Worthen.